Estimating the cost of implementing a facility and community score card for maternal and newborn care service delivery in a rural district in Uganda - Ssebagereka, Anthony; Apolot, Rebecca Racheal; Nyachwo, Evelyne Baelvina; Ekirapa-Kiracho, Elizabeth (International Journal for Equity in Health, 2021)
This paper aimed at estimating the resources required to implement a community Score Card by a typical rural district health team in Uganda, as a mechanism for fostering accountability, utilization and quality of maternal and child healthcare service.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; community scorecard (CSC) / cartão de pontuação comunitária (CPC); gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; youth / juventude

Introduction: The Accountability Politics of Reducing Health Inequalities: Learning from Brazil and Mozambique - Waisbich, Laura Trajber; Shankland, Alex; Bloom, Gerald; Coelho, Vera Schattan P.; Waisbich, Laura Trajber; Shankland, Alex; Bloom, Gerald; Coelho, Vera Schattan P. (Novos estudos CEBRAP, 2019)
Inequality is a key political issue of our times. It has political consequences, fuelling conflict and raising legitimacy chal‑ lenges for regimes around the world, in democratic and non‑demo‑ cratic settings alike. At the centre of these challenges is the question of accountability: who can be held accountable, on what basis, how and by whom for tackling or failing to tackle which inequalities. In the field of global health, inequality has long been a key issue. A significant body of work — in global health and health systems research — has approached the issue of health inequalities and in‑ equities by highlighting the role of social determinants (Marmot, 2015; Wilkinson; Pickett, 2006; Barreto, 2017). A more recent and less developed stream of work frames them in terms of political de‑ terminants: in other words, seeing them as issues that may be ad‑ dressed through politics as well as policy.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; health / saúde

Health provider responsiveness to social accountability initiatives in low- and middle-income countries: a realist review - Lodenstein, Elsbet; Dieleman, Marjolein; Gerretsen, Barend; Broerse, Jacqueline E W (Health Policy and Planning, 2017)
Social accountability in the health sector has been promoted as a strategy to improve the quality and performance of health providers in low- and middle-income countries. Whether improvements occur, however, depends on the willingness and ability of health providers to respond to societal pressure for better care. This article uses a realist approach to review cases of collective citizen action and advocacy with the aim to identify key mechanisms of provider responsiveness. Purposeful searches for cases were combined with a systematic search in four databases. To be included in the review, the initiatives needed to describe at least one outcome at the level of frontline service provision. Some 37 social accountability initiatives in 15 countries met these criteria. Using a realist approach, retroductive analysis and triangulation of methods and sources were performed to construct Context–Mechanism–Outcome configurations that explain potential pathways to provider responsiveness. The findings suggest that health provider receptivity to citizens’ demands for better health care is mediated by health providers’ perceptions of the legitimacy of citizen groups and by the extent to which citizen groups provide personal and professional support to health providers. Some citizen groups activated political or formal bureaucratic accountability channels but the effect on provider responsiveness of such strategies was more mixed. Favourable contexts for health provider responsiveness comprise socio-political contexts in which providers self-identify as activists, health system contexts in which health providers depend on citizens’ expertise and capacities, and health system contexts where providers have the self-perceived ability to change the system in which they operate. Rather than providing recipes for successful social accountability initiatives, the synthesis proposes a programme theory that can support reflections on the theories of change underpinning social accountability initiatives and interventions to improve the quality of primary health care in different settings.
Keywords: *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde

Introduction: Accountability through Participation: Developing Workable Partnership Models in the Health Sector - Cornwall, Andrea; Lucas, Henry; Pasteur, Kath (IDS Bulletin, 2000)
The IDS Participation and Health and Social Change Groups convened a workshop in October 1999 to share experience with the use of participatory approaches in enhancing accountability in the health sector, and to explore some of these challenges. The articles in this bulletin reflect some of the richness of experience on the ground in building effective participation, as well as some of the many issues that arise in moving towards more active citizen engagement with service provision. They bring experience from current and ongoing work to reflect on the links between participation, accountability and improvements in health. The workshop explicitly aimed to reflect on experiences that were moderately successful, in order to identify potential elements that contribute to and impede the success of efforts to build accountability through participation. It is important to emphasise that understanding of the complexities of this approach is at a very early stage. The design of interventions is complex and often highly contextdependent. Rather than attempt to establish any blueprint for future activities, the workshop sought to explore the issues and attempt to advance the debate. In this introduction we draw out some of the principal themes emerging from the articles included here, and from workshop discussions.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; health / saúde